Optimizing archival management through an internship program at Sekretariat Jenderal DPR RI - Najwa Nabila (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2025)
Archival management plays an important role in supporting administrative functions in government institutions. However, it often faces various challenges, particularly in managing inactive dynamic records that are infrequently used but may need to be retrieved when required. This community service aims to analyze the optimization of archival management through an internship program undertaken by students in the archival field at the Sekretariat Jenderal DPR RI. The study employed a qualitative descriptive approach using observation, documentation, and literature review. The findings indicate that students actively contributed to archival management, particularly in records arrangement, archival media conversion, archival handling, data entry via the Sistem Informasi Kearsipan Nasional (SIKN) website, and the development of innovative projects through information repackaging. The conclusion indicates that the internship program makes a positive contribution to archival management within the institution. Despite several technical constraints, the internship activities were conducted effectively and provided students with new insights and skills in the field of archives. To enhance the effectiveness of future archival management, this community service recommends harmonizing archival guidelines and increasing attention to the physical condition of records to prevent damage.   Abstrak Pengelolaan arsip memiliki peran penting dalam mendukung penyelenggaraan administrasi pada lembaga pemerintahan. Namun, pengelolaan arsip masih sering menghadapi berbagai kendala, khususnya dalam mengelola arsip dinamis inaktif yang frekuensi penggunaannya jarang, tetapi sewaktu-waktu dapat dicari kembali ketika dibutuhkan. Pengabdian ini bertujuan untuk menganalisis optimalisasi pengelolaan arsip melalui kegiatan magang yang dilakukan oleh mahasiswa pada bidang kearsipan di Sekretariat Jenderal DPR RI. Metode yang digunakan adalah pendekatan deskriptif kualitatif melalui observasi, dokumentasi, serta studi pustaka. Temuan pengabdian menunjukkan bahwa mahasiswa berkontribusi aktif dalam pengelolaan arsip, terutama dalam penataan arsip, alih media arsip, manuver arsip, penginputan arsip melalui website (Sistem Informasi Kearsipan Nasional) SIKN, serta pembuatan proyek inovasi berupa kemas ulang informasi. Kesimpulan menunjukkan bahwa program magang memberikan kontribusi positif dalam mendukung pengelolaan arsip pada lembaga terkait. Meskipun terdapat beberapa kendala teknis, kegiatan magang terlaksana secara efektif dan memberikan wawasan serta keterampilan baru di bidang kearsipan bagi mahasiswa. Dalam meningkatkan efektivitas pengelolaan arsip ke depannya, pengabdian ini merekomendasikan agar lembaga terkait menyelaraskan pedoman kearsipan yang digunakan serta meningkatkan perhatian terhadap kondisi fisik arsip guna mencegah kerusakan. Kata Kunci: arsip dinamis inaktif; pengelolaan arsip; program magang mahasiswa; SIKN